PENGARUH PER, DER, PBV TERHADAP HARGA SAHAM DENGAN EPS SEBAGAI MODERASI - Sarfio, Efrina Marsella; Setijaningsih, Herlin Tundjung (Jurnal Paradigma Akuntansi, 2025)
This study aims to determine the effect of Price Earning Ratio (PER), Debt Equity Ratio (DER), Price to Book Value (PBV) on moving share price in energy companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period, with Earning Per Share (EPS) as a moderating variable. In this study, there were 38 energy companies as a sample in which moderation regression analysis was performed. This study uses a purposive sampling technique with a total of 93 data in three years, and the data used in this study is secondary data obtained from financial reports. the research data was processed using IBM SPSS 26 and Microsoft Excel 2019. The results of this study indicate that the price earning ratio has a negative and insignificant effect on share prices; debt equity ratio has a positive and insignificant effect on share price; and price to book value has a positive and significant influence on share price. Furthermore, Earning Per Share (EPS) as a moderator can weaken the effect of Debt Equity Ratio (DER) and Price to Book Value (PBV) on share price but company size cannot moderate the effect of company growth on share price. The implications of this research are as a reference source for research related to share price and can support signal theory and can also make a positive contribution related to stock prices as a material consideration for investors before making investment decisions.